2016
DOI: 10.1007/s10853-016-9837-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress measurement using area detectors: a theoretical and experimental comparison of different methods in ferritic steel using a portable X-ray apparatus

Abstract: Using area detectors for stress determination by diffraction methods in a single exposure greatly simplifies the measurement process and permits the design of portable systems without complex sample cradles or moving parts. An additional advantage is the ability to see the entire or a large fraction of the Debye ring and thus determine texture and grain size effects before analysis. The two methods most commonly used to obtain stress from a single Debye ring are the so called cos α and full-ring fitting method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…However, only cos is chosen in this study as a representative of two-dimensional methods because the fundamental equation of the XRD 2 method is basically identical to equation 7, and it measures only part of the Debye ring (Miyazaki & Sasaki, 2016), while the cos and full-ring methods use all of the information. We have also shown experimentally that, when using the same dataset, there was no difference between the cos and full-ring fitting methods (Ramirez-Rico et al, 2016).…”
Section: The Cos a Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…However, only cos is chosen in this study as a representative of two-dimensional methods because the fundamental equation of the XRD 2 method is basically identical to equation 7, and it measures only part of the Debye ring (Miyazaki & Sasaki, 2016), while the cos and full-ring methods use all of the information. We have also shown experimentally that, when using the same dataset, there was no difference between the cos and full-ring fitting methods (Ramirez-Rico et al, 2016).…”
Section: The Cos a Methodsmentioning
confidence: 62%
“…1(b). We previously reported that the strain precision of this portable machine is about 9 microstrain (m") with ferrite reference powders (Ling & Lee, 2015), and that in essence the sin 2 and cos methods are theoretically identical (Ramirez-Rico et al, 2016) and yield statistically indistinguishable experimental results (Ramirez-Rico et al, 2016;Ling & Lee, 2015). The mathematical equivalency between sin 2 and cos was also shown very recently (Miyazaki & Sasaki, 2016).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Out of this data the residual stress is calculated. Two different methods (sin 2 Ψ-2θ-method [3] and cosα-method [4]) are common. Both methods are compatible and here it is not important difference, which method is used [5;6].…”
Section: Basicsmentioning
confidence: 99%
“…Main chemical compositions of AA2050 (wt.%). The surface residual stress results were calculated by cos α method according to strain data determined from the Debye-Scherrer ring[25]. The data were obtained in about 10 µm depth of the surface area.…”
mentioning
confidence: 99%